Peningkatan Kinerja Guru melalui komitmen terhadap profesi (penelitian pada Guru PAI di SMK IT AISYIYAH Jakarta) - Asri Andriana Lituhayu; Raden Roro Vemmi Kesumadewi; Mariatuzzahro (STIT Sirojul Falah Bogor, 2025)
This study aims to determine the efforts to improve performance through a study of the direct influence of the variables of commitment to the profession, The selected sample amounted to 85 people using stratified proportional random sampling with the Cochran formula. This study uses a survey method with a SITOREM analysis. The results of this study conclude that: (1) There is a direct influence of empowerment on teacher performance with a value 0.342. The results of the SITOREM analysis show that the indicators that are still weak and need to be improved are; 1) competency development, 2) organizational support, 3) communication between subordinates and superiors, 4) flexibility in work. Keywords: leadership, organizational management, teacher performance.